Protective effect of active and nano-naringenin on methotrexate -induced oxidative stress in male rats’ reproductive system - Al Bayati, Huda S. Shehab-ALdeen; Al Zubaidi, Bushra Abbas (Journal of Kerbala for Agricultural Sciences, 2024)
In this study, which aimed to determine the preventive effect of Naringenin extracted from citrus aurantifolial on the damage caused by the methotrexate, in which 30 male rats were used, divided into five groups, which were control group dosed with Normal Saline (G1), second group dosed with methotrexate (G2) , third group dosed with Naringenin (15 to 15.5 mg) (G3), four group dosed with methotrexate and active Naringenin (G4) , fifth group dosed with methotrexate and Naringenin nanoparticles (G5) for two months, it was found that significantly increase the level of sex hormones and sperm parameters in G3 , G5 compared to G2 . It was also found that active Naringenin , Naringenin nanoparticles works to repair damage to the tissues of the testicles, epididymis and accessory glands caused by methotrexate the experimental group administered with G3,G4 and G5 had a typical testicular tissue shape characterized by tubules. Spermatozoa exhibit an elliptical morphology and are organized in a systematic and orderly fashion. the basement membrane envelops each tubule and contains sperm-generating cells, including dispersed Sertoli cells with triangle nuclei sperm progenitors In conclusion, the results of this article revealed It was found that Naringenin alone and Naringenin nanoparticles with the drug gave the best results on the methotrexate -induced male rats reproductive system